Structural Problems in the Development of Social Work in Central Europe under Transformation. The Case of Poland - Jerzy Szmagalski (Social Work and Society, 2004)
Socio-economic transformation the countries of Central Europe are undergoing since 1989 has brought new developments in social welfare systems of this region. Social work, which was in the countries of the region during its communist past either non-existent or superficial activity, has become treated as an instrument of social welfare systems there. The collapse of authoritarian regimes in the region clearly inducted political leaderships there to opt for transition to Western style civil society. Hence an adoption of social work seemed to be natural choice for the countries in the region.